Perubahan Nilai Cerna dan Fraksi Protein pada Susu Kedelai dalam Proses Pembuatan Soygurt - Yusmarini Yusmarini; Mochammad Adnan; Suwedo Hadiwiyoto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2001)
This research investigated the effect of fermentation of soymilk by Streptococcus thermophilus and Lactobacillus acidophilus on the digestibility and protein fractions of the soygurt. The studies were conducted in three steps : (1) soymilk production, (2) soygurt production, and (3) chemical analysis of soymilk and soygurt. It is found that fermentation stimulated by addition of sucrose in the substrate increased the digestibility of protein. Electrophoretic pattern of the protein showed that only minor changes occured during the fermentation of soymilk into soygurt.